Challenges for urban sustainable mobility: Gdynia Maritime University case study - Michał Kuzia; Adam Przybyłowski (Economic and Environmental Studies (E&ES), 2017)
The sustainable development of the cities represents one of the major challenges for the future of the planet in the 21st century, relatively to the contribution and adaptation to climate change, natural resources consumption, energetic transition, population mobility, welfare and security, pollution, the global economic growth. Tri-City, as many of contemporary agglomerations, faces lots of challenges connected with human negative impact on the environment, health and the city space. The mobility of people is one of them. The quality of transport in Gdansk, Gdynia and Sopot is getting worse because of the excessive use of cars, non-integrated public transport system, insufficient use of ecological transport, as well as uncontrolled urban sprawl. The objective of the paper is to present sustainable mobility planning challenges in the agglomerations at the example of seaport city Gdynia. To check the necessity of creating a new mobility pattern for important traffic generators, a research study has been carried out. The pilot survey research has been made among the staff and students of one of the biggest institutions in the city - Gdynia Maritime University. The research tool was based on an anonymous questionnaire containing a set of questions such as: the use of mode of transport, transit and parking problems, as well as the awareness of sustainable mobility. The survey results indicate that there is an unsustainable model of travelling among the academic community and transport's behavior should be changed in order to implement the sustainable mobility concept in practice.
Keywords: N74; O18; R11; R41; R42; 330; contemporary agglomerations' challenges; sustainable development; urban mobility; transport system